A proposal to integrate teacher digital competencies and professional knowledge associated with PCK and TPACK - Girotto Júnior, Gildo Girotto; Morais, Carla; Fernandes Goes, Luciane; Gonçalves Costa, Guilherme (Góndola, enseñanza y aprendizaje de las ciencias, 2025)
Teacher training for the use of technological resources has been widely researched in educational studies. Situated in the context of such investigations, research on digital competences in education has also gained prominence in the last decade. Considering the breadth of work conducted in these areas and the need for integration between the different theoretical-practical domains that permeate this field of study, the main objective of this research is to develop a theoretical framework to bridge the references of teaching and digital competency within Teaching Professional Knowledge. Methodologically, a systematic literature analysis was conducted, beginning with an initial bibliometric analysis using VOSviewer software tool, followed by the categorization of a selected corpus of works. Subsequently, an analysis of the relationships between the teaching of digital competences and the knowledge domains related to the references of Pedagogical Content Knowledge and Pedagogical and Technological Content Knowledge was carried out. The systematic review allowed us to infer that prevailing trends in research on the teaching of digital competency are related to the assessment of competences in different groups of teachers, to the proposal of training actions, and to theoretical studies. It was evident that the theoretical framework known as DigCompEdu serves as a foundation for various research endeavors. Relations between the domains of teaching professional knowledge and digital competences were identified, and based on this identification, a theoretical framework is discussed and proposed to consider the possibility of articulating actions for the development of teaching digital competences in the context of teacher training oriented towards Pedagogical and Technological Content Knowledge.